ANALISIS DIET TINGGI KALORI TINGGI PROTEIN (TKTP) PADA PENDERITA TB PARU RAWAT INAP DI RUMAH SAKIT MARTHA FRISKA PULO BRAYAN TAHUN 2012 - Hermi Nainggolan; Evawany Y Aritonang; Mhd.Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Diet given to patient lung tuberculosis is diet high calories high protein (HCHP). Diet high calories high protein given after diagnosis patient upheld. Diet high calories high protein was that contain energy and protein above the needs of the normal. Component nutrition of the major diet is energy, proteins, fat and carbohydrates. Component nutrition diet is very important to buttress healing process on the patient lung tuberculosis. The purpose of this study is food in the form diet High Calories High Protein (HCHP) patients treated in the Lung Tuberculosis Hospital Martha Friska Pulo Brayan. This research design is descriptive research account with design cross sectional of dietary by the department of nutrition Hospital Martha Friska Pulo Brayan. There was a 15 sample diet by the criteria High Calories High Protein I (HCHP I) diet. The research results showed that avaibility of nutritive substance, diet the content of energy, protein, fat and carbohydrates are not meet the standards on diet high colories high protein (HCHP). It is caused by the absence of standards, the portion standards recipes and standards of tool used. Energy requirement of 39%-67%, protein requirement of 39%-68%, fat requirement of 51%-80% and carbohydrate requirement of 25%-71% of standards. Keywords: Lung Tuberculosis, diet High Calories High Protein (HCHP)